Red-eyed tree frog - Cowley, Joy.; Bishop, Nic, 1955- (New York : Scholastic Press, 1999)
This frog found in the rain forest of Central America spends the night searching for food while also being careful not to become dinner for some other animal.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Children.
2.8
K-3
Keywords: Hylidae -- Central America -- Juvenile literature; Frogs; Tree frogs; Frogs; Tree frogs